What is Islamic Management? A Previous Studies - Syahdatul Maulida; Aam Slamet Rusydiana (Management and Sustainability, 2022)
This study aims to determine the development map of Islamic Management based on Scopus indexed journals. The analyzed data includes 369 indexed research publications. The export data is then processed and analyzed using the R Biblioshiny application program to identify the bibliometric map of the development of Islamic management. The results show that the number of publications on the development of the role of Islamic management research has increased significantly. The results also show that the most types of documents are journal articles. Journal of Islamic Accounting and Business Research is the top journal. The most famous authors are Hassan MK, Alam MK, Rahman MM, Haron R, Sukmana R, Ascarya A, Abd Wahab N, and Ali M, and the most popular keyword topic is Islamic banks with the popular theme of financial. Then, five research clusters were also obtained based on the topic of Islamic management.